Memetakan Konfigurasi Ekologi Dakwah di Kota Surabaya - Nurdin, Ali; Rahmawati, Pudji (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
Ecology of da'wah is the integration of envi-ronmental aspects with Islamic values in da'wah. The citizen of Surabaya has an uncharted ecological potential. This study attempts to map the the elements of preaching ecology in Surabaya such as the potential of preachers, da'wah messages, proselytising methods, the proselytism object (mad'u) , media of proselytising, mosques, prayer rooms, and majelis taklim . By using qualitative-descriptive methods, the results of this study revealed that Muslim proselytisers have a very dominant role in empowering religiosity of society, however, the da'i-mad'u ratio is not adequate for the needs. Further, the da'wah message delivered by da'i seems did not meet a standardized da'wah curriculum. The majority of preachers also use one-way communication while preaching and only a small number of them provided a question-and-answer session. Mean-while, the ratio of the number of Muslims to religious facilities was 513: 1.